146k views
0 votes
Factor the expression over the complex numbers.


x^(2) +18

User Yamu
by
5.5k points

2 Answers

2 votes

Answer:


(x+3i√(2))(x-3i√(2))

Explanation:

1. You must apply the Quadratic formula, which is:


x=\frac{-b+/-\sqrt{b^(2)-4ac} }{2a}

2. Substitute values:


a=1\\b=0\\c=18


x=\frac{-0+/-\sqrt{0^(2)-4(1)(18)} }{2(1)}\\x=(+/-√(-72))/(2)\\x=(+/-6i√(2))/(2)\\x=+/-3i√(2)

3. Finally, you obtain:


(x+3i√(2))(x-3i√(2))

User Miki
by
5.5k points
3 votes

Here we are given the expression:


x^(2)+18

Now let us equate it to zero to find x first,


x^(2)+18=0

Now subtracting 18 from the other side,


x^(2)=-18

taking square root on both sides,

So we will get two values of x as ,


x=3√(-2)


x=-3√(-2)

Now we can write square root -1 as i,

So our factors become,


x=3i√(2)


x=-3i√(2)

Answer:

The final factored form becomes,


(x+3i√(2))(x-3i√(2))



User ShlomiF
by
5.3k points